INSURANCE AS A FORM OF SOCIAL PROTECTION FOR WOMEN INDONESIAN MIGRANT WORKERS - Hekmatyar, Versanudin; Istianah, Istianah (Indonesian Journal of Social Work, 2023)
Social protection is a right obtained by the migrant workers. Based on statistics in 2019, the number of women migrant workers was 44% higher than men migrant workers. Social protection is a guarantee provided by the government to protect its citizens who work both in country and abroad. This study aims to describe how women migrant workers interprets the social protection provided to them, especially related to health insurance. Health insurance is an obligation of the government, both the government of the country of origin and the recipient country for workers. This research was conducted on 5 women migrant workers in Hong Kong. The women migrant workers are them who are currently working or who have returned to Indonesia either because of the contract period has ended or because of layoffs. The study demonstrates three meanings of social protection for women migrant workers: assistance, security, and equity. Women migrant workers are able to interpret the social protection based on their experiences.